(untitled) (Contemporary Journal of Social Science Review, 2025)
This study investigates the interpretive role of the translator in the Urdu translation of Elif Shafak’s novel The Forty Rules of Love, titled Chalis Charag Ishq kay. Employing a qualitative and comparative research design, the analysis is grounded in André Lefevere’s theory of Rewriting. The research examines how the translator, Huma Anwar, functions not merely as a linguistic converter but as a cultural interpreter, navigating the complex transference of meaning between the source and target texts. Central to this inquiry are the challenges of translatability and accuracy, particularly concerning the novel’s core themes of Sufism and mystical love. The study demonstrates that the translator actively mediates cultural and ideological differences, making the source text’s knowledge accessible and meaningful for the Urdu-speaking readership. By applying Lefevere’s concepts of refraction and patronage, alongside other translation strategies, this article elucidates the deliberate rewritings that occur to align the work with the target culture’s poetics and ideological framework, ultimately shaping its reception.